PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, PENDAPATAN ASLI DAERAH, DAN DANA BAGI HASIL TERHADAPBELANJA MODAL (SURVEY PADA KABUPATEN/KOTA DI SULAWESI TENGAH) - Sarif, Mohamad (Katalogis, 2017)
The study is aimed to determine and analyze the development of general allocation funds, specific allocation funds, local earning, sharing revenue, and capital expenditure, and also the influence of general allocation funds, specific allocation funds, local earning, sharing revenue on capital expenditure, both simultaneously and partially. Sample consists of 11 districts/cities in Central Sulawesi with 55 observation points selected through purposive sampling. Method of data analysis is trends analysis and multiple linear regressions with SPSS 16.0 version for windows. The results find out that realization of general allocation funds, local earning, and capital expenditure in 5 years averagely is increasing, however, realization of specific allocation funds and sharing revenuefluktuates. Simultaneous test shows that general allocation funds, specific allocation funds, local earning, sharing revenue simultaneously have influence on capital expenditure. Partial test shows that specific allocation funds and local earning have significant influence on capital expenditure while general allocation funds and sharing revenue have insignificant influence on capital expenditure. Determination coefficient R-Square value of 0.546 indicates that 54.60% of capital expenditure is influence by variables of specific allocation funds and local earning and the rest is influenced by variables that are not studies.